Virtue of love in educational heritage of M. Реčkаuѕkаitė - Tijūnelienė, Ona (Acta Paedagogica Vilnensia, 1998)
In this article it is shown that M. Pečkauskaitė, representative of the Lithuanian Catholic pedagogy, treats love as a virtue in her works. God’s love is the source of love for different things. When faith is strong, so the virtue of man is also strong. Mothers who want to educate their children as moral children must teach the faith. Mother has a strong power of love – without this love the most beautiful feelings do not develop in the mind of a child. To love one’s neighbour is the best virtue. Love of motherland is given by the God to the people as a duty. Hence, it is important to love in all matters at home every day. Every human being must learn to love. The virtue of love should become an ideal for all.